Colaboração interprofissional entre as equipes de saúde na transferência do cuidado nos serviços de urgência e emergência - Miorin, Jeanini Dalcol (2023)
The main objective is to analyze interprofessional collaboration between health teams in the transfer of pre-hospital care. This is research with a qualitative approach, of the case study type, based on D'Amour's model of interprofessional collaboration. The case study was carried out in the Mobile Emergency Care Service (SAMU) in the municipality of Santa Maria-RS and in the destination services for the transfer of care carried out by SAMU, these being: the 24-Hour Emergency Care unit (UPA) , the Municipal Emergency Service (PAM) and Emergency Room (PS). Data were collected from February 2021 and from April to August 2021; aiming at triangulating sources of evidence, based on documentary research, interviews and systematic observation. The data was assessed through thematic content analysis and was referenced in D'Amour's typology of interprofessional collaboration. The service bulletins delivered by SAMU to the service and the nursing and medical developments after the patient was received by SAMU were analyzed. 44 professionals were interviewed, including doctors, nurses, nursing technicians/aides from the aforementioned services and SAMU ambulance drivers, and a total of 449 hours of observation were carried out with the teams. The findings of this study allowed the organization of the results into three manuscripts. The first was composed of two thematic categories that revealed difficulties in the development of collaborative practices, such as a lack of knowledge of the functioning of other services and professional skills and of dialogue and motivation between teams. The second manuscript formed two categories that revealed the incomplete exchange of information between the teams and the lack of standardization, in addition to inefficient means of communication. There is little effort by some managers to provide an organizational environment that strengthens interprofessional collaboration in the transfer of pre-hospital care. The third manuscript showed interprofessional collaboration in development in the transfer of pre-hospital care. This indicates timid transformations in professional practices, especially linked to leadership attitudes, which favored the political action of managers in the development of interprofessional collaboration, which culminated in the creation of formal and informal agreements. From the results it was concluded that there are some transformations in professional practices, however it can be said that interprofessional collaboration was not effectively demonstrated in organizations and between professionals, which can result in services that are less efficient.